Formulation and Testing of In Vivo Anti-Inflammatory Activity of Ethanol Extract Cream from Plumeria rubra L. Leaves for Topical Skin Inflammation - aftahul hajlina; Erida Novriani; Asyrun Alkhairi Lubis (MEDFARM: Jurnal Farmasi dan Kesehatan, 2026)
Skin inflammation in Indonesia has a prevalence of up to 6.8%, with corticosteroids being the primary treatment despite risking serious long-term side effects. This study aims to formulate and evaluate the topical anti-inflammatory and tissue-repair activity of an ethanol extract cream of Plumeria rubra L. leaves as a natural alternative. The extract was obtained through maceration with 96% ethanol and formulated into an oil-in-water (O/W) cream at concentration variations of 2% (F1), 4% (F2), and 6% (F3). Phytochemical screening revealed that the extract contains alkaloids, flavonoids, saponins, tannins, terpenoids, and steroids. Physical evaluation demonstrated that the preparations are stable, homogeneous, possess standard pharmaceutical spreadability and adhesion, and maintain an ideal skin-compatible pH range (4.5–5.24). In vivo anti-inflammatory evaluation in white rats showed a significant difference in healing by day 9 (p < 0.05). Formula F2 (4%) yielded the most optimal results, exhibiting the smallest average wound length of 0.64 ± 0.11 cm and a healing time of 9.00 ± 0.00 days, which was statistically equivalent to the positive control. Increasing the concentration to 6% (F3) did not provide a significant acceleration in healing, indicating a saturation concentration phenomenon. In conclusion, the Plumeria rubra L. leaf extract cream at a 4% concentration is the most efficient and effective formula for accelerating wound healing and treating skin inflammation.